Induced gratitude and hope, and experienced fear, but not experienced disgust, facilitate COVID-19 prevention - Russell, Pascale Sophie; Frackowiak, Michal; Cohen-Chen, Smadar; Rusconi, Patrice; Fasoli, Fabio (Cognition and emotion, 2023)
Hope, gratitude, fear, and disgust may all be key to encouraging preventative action in the context of COVID-19. We pre-registered a longitudinal experiment, which involved monthly data collections from September 2020 to September 2021 and a six-month follow-up. We predicted that a hope recall task would reduce negative emotions and elicit higher intentions to engage in COVID-19 preventative behaviours. At the first time point, participants were randomly allocated to a recall task condition (gratitude, hope, or control). At each time point, we measured willingness to engage in COVID-19 preventative behaviours, as well as experienced hope, gratitude, fear, and disgust. We then conducted a separate, follow-up study in February 2022, to see if the effects replicated when COVID-19 restrictions were relaxed in the UK. In the main study, contrary to our pre-registered hypothesis, we found that a gratitude recall task elicited more willingness to engage in COVID-19 preventative behaviours in comparison to the neutral recall task. We also found that experienced gratitude, hope, and fear were positively related to preventative action, while disgust was negatively related. These results present advancement of knowledge of the role of specific emotions in the COVID-19 pandemic.